SURVEI FAKTOR KESULITAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS RENDAH SEKOLAH DASAR - Wynne Stevania Iryani; Syarif Sumantri; Linda Zakiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is key in facing the changes of time, yet the issue of illiteracy still prevails in Indonesia. Bahasa Indonesia plays a crucial role in education, especially in developing students' writing skills in elementary school. This research employs a survey method to identify the factors contributing to low writing proficiency among elementary school students. The findings indicate that intellectual, psychological, and environmental factors play significant roles. Holistic and inclusive teaching strategies, along with increased support for educators, are necessary to enhance students' writing abilities at the elementary school level. Pendidikan adalah kunci dalam menghadapi perubahan zaman, tetapi masalah buta aksara masih merajalela di Indonesia. Bahasa Indonesia memegang peran penting dalam pendidikan, terutama dalam mengembangkan kemampuan menulis siswa di sekolah dasar. Penelitian ini menggunakan metode survei untuk mengidentifikasi faktor-faktor kesulitan menulis siswa kelas rendah. Hasilnya menunjukkan bahwa faktor intelektual, psikologis, dan lingkungan memainkan peran penting. Diperlukan strategi pembelajaran yang holistik dan inklusif serta peningkatan dukungan bagi pendidik untuk meningkatkan kemampuan menulis siswa di tingkat Sekolah Dasar.